2019
DOI: 10.1007/s41999-019-00244-7
|View full text |Cite
|
Sign up to set email alerts
|

What is geriatric rehabilitation and how should it be organized? A Delphi study aimed at reaching European consensus

Abstract: Aim To reach European Consensus on Geriatric Rehabilitation using a modified Delphi Procedure. Findings Consensus was reached on 61 statements on a broad range of topics. Message This consensus is important to facilitate exchange of best practice and compare results of scientific research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 16 publications
2
44
0
Order By: Relevance
“…The indications for inclusion into GR were similar across countries and comprise mainly geriatric syndromes and their negative impacts [10]. The core GR team composition, comprising a geriatrician or skilled elderly care physician, nurses and physiotherapists, was also similar across Europe and matched the findings of previous Delphi study [11]. Wide differences in length of stay between countries are explained by the different settings and forms of GR, the different ways it is conducted, as well as the way that GR is funded and regulated in different countries.…”
Section: Discussionsupporting
confidence: 64%
“…The indications for inclusion into GR were similar across countries and comprise mainly geriatric syndromes and their negative impacts [10]. The core GR team composition, comprising a geriatrician or skilled elderly care physician, nurses and physiotherapists, was also similar across Europe and matched the findings of previous Delphi study [11]. Wide differences in length of stay between countries are explained by the different settings and forms of GR, the different ways it is conducted, as well as the way that GR is funded and regulated in different countries.…”
Section: Discussionsupporting
confidence: 64%
“…The aim of this systematic literature review and metaanalysis was to present an overview of the nutritional status on admission and its association with functional parameters in geriatric rehabilitation patients. The pooled prevalence (95% CI) for MNA (nine studies) demonstrated that malnutrition and risk of malnutrition were present in 13% (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) and 47% (40-54) of the geriatric rehabilitation population, whereas the pooled estimate (95% CI) of BMI (n = 45) was 23.8 kg/m 2 (23.2-24.5). The ranges of the values and heterogeneity were high among the individual studies of the respective pooled estimates.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the nutrition-related diseases sarcopenia and frailty [12] are highly prevalent in this population [13,14]. The goal of geriatric rehabilitation is to stimulate functional recovery and thereby allow patients to return to their homes [11,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The preparation stage comprised two Delphi studies, one about the definition and organisation of GR in Europe [3], and one about the structures for GR across Europe [4]. These are reported in detail elsewhere.…”
Section: Methodsmentioning
confidence: 99%